2023
DOI: 10.1177/13524585231200720
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillar-associated protein 4 as a potential marker of acute relapse in inflammatory demyelinating diseases of the central nervous system: Pathological and clinical aspects

Sara Samadzadeh,
Mads Nikolaj Olesen,
Martin Wirenfeldt
et al.

Abstract: Background: Microfibrillar-associated protein 4 (MFAP4) is an extracellular matrix protein not previously described in the human central nervous system (CNS). Objectives: We determined MFAP4 CNS expression and measured cerebrospinal fluid (CSF) and serum levels. Methods: Tissue was sampled at autopsy from patients with acute multiple sclerosis (MS) ( n = 3), progressive MS ( n = 3), neuromyelitis optica spectrum disorder (NMOSD) ( n = 2), and controls ( n = 9), including 6 healthy controls (HC). MFAP4 levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Notably, in autopsy samples from patients with acute multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD), we observed a downregulation of MFAP4 immunoreactivity at sites of active inflammation documented by the presence of inflammatory infiltrates. In line with these pathology data, cerebrospinal fluid (CSF) MFAP4 levels were reduced in active disease stages (27). The data suggested that inflammation changes the composition of ECM, perhaps due to the secretion of proteolytic enzymes e.g., MMPs in inflammatory conditions.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Notably, in autopsy samples from patients with acute multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD), we observed a downregulation of MFAP4 immunoreactivity at sites of active inflammation documented by the presence of inflammatory infiltrates. In line with these pathology data, cerebrospinal fluid (CSF) MFAP4 levels were reduced in active disease stages (27). The data suggested that inflammation changes the composition of ECM, perhaps due to the secretion of proteolytic enzymes e.g., MMPs in inflammatory conditions.…”
Section: Discussionsupporting
confidence: 65%
“…MFAP4 is measurable in serum, serum levels increase in specific conditions characterized by aberrant tissue remodeling (26) while ECM-bound MFAP4 is predominantly located in arteries and arterioles in most tissues (17). Very recently our group reported data on expression of MFAP4 in the CNS and alteration of the levels of soluble MFAP4 in cerebrospinal fluid (CSF) in patients with acute neuroinflammation and relapse (27). These data suggest that MFAP4 may serve as a potential biomarker of disease activity.…”
Section: Introductionmentioning
confidence: 99%